2017
DOI: 10.1186/s13613-017-0322-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of in- and out-of-hospital cardiac arrest survivors with liver cirrhosis

Abstract: BackgroundOrgan failure increases mortality in patients with liver cirrhosis. Data about resuscitated cardiac arrest patients with liver cirrhosis are missing. This study aims to assess aetiology, survival and functional outcome in patients after successful cardiopulmonary resuscitation (CPR) with and without liver cirrhosis.MethodsAnalysis of prospectively collected cardiac arrest registry data of consecutively hospital-admitted patients following successful CPR was performed. Patient’s characteristics, admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 44 publications
4
34
1
1
Order By: Relevance
“…Mortality in our critically ill patients with cirrhosis was high (>50% died within 1 year following ICU admission), which is comparable to earlier studies in this field . In keeping with the literature, lactate levels were associated with poor outcome in our patients with cirrhosis (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Mortality in our critically ill patients with cirrhosis was high (>50% died within 1 year following ICU admission), which is comparable to earlier studies in this field . In keeping with the literature, lactate levels were associated with poor outcome in our patients with cirrhosis (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…SOFA, median (IQR) 11 (7)(8)(9)(10)(11)(12)(13)(14) CLIF-SOFA, median (IQR) 12 (8)(9)(10)(11)(12)(13)(14)(15) CLIF-C ACLF score, median (IQR) 53.6 (45.0-61. (P < 0.01 for all).…”
Section: Part 1: Lactate Levels In Critically Ill Patients With Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated that patients with shockable rhythms have higher odds of survival after receipt of in‐hospital CPR compared to those with non‐shockable rhythms . Hospitalized patients with cirrhosis are less likely to have a cardiac aetiology of their cardiac arrests and are more likely to have an initial non‐shockable rhythm of pulseless electrical activity or asystole . Unfortunately, we do not have specific data on the aetiology of cardiac arrest in this cohort.…”
Section: Discussionmentioning
confidence: 91%
“…Of all cardiac arrests in patients with pulmonary hypertension, 50% are due to the progression of the underlying disease, so this complication must be prevented from occurring in the first place due to the very low chance of recovery [ 15 ]. Similarly for patients with cirrhosis, cardiac arrest is a marker of a very poor prognosis; in one study, only 19% of these patients survived and of these patients, most had very poor neurological recovery 1 month after surviving cardiac arrest [ 16 ].…”
Section: Discussionmentioning
confidence: 99%